Aminoglycoside toxicity in neonates: something to worry about?. Issue 3 (March 2014) - Kent, Alison; Turner, Mark A; Sharland, Mike; Heath, Paul T
<x xml:space="preserve">Abstract</x> Toxicity has limited the use of aminoglycosides and adult studies report high rates of both ototoxicity and nephrotoxicity. Conversely paediatric studies have shown lower rates and extended interval dosing may have reduced toxicity further. We review the animal and human evidence for aminoglycoside toxicity in neonates including mechanisms, measurement and rates of toxicity; and differences between aminoglycosides and dosing regimens. We discuss genetic susceptibility and the impact of other synergistic effects.